2009
DOI: 10.1111/j.1468-2419.2009.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Management development in China: a policy analysis

Abstract: This study analyzes the current structure of Chinese management development (MD) policy. It identifies three critical challenges facing Chinese managers and reviews related MD policies. It considers the evolution of major MD-related policies in the context of broader social, economic and institutional changes in China. Five principal findings inform the conclusion that with the experience accumulated in three decades of reform practices, MD policy in China should no longer be based on the principle of 'groping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Another empirical analysis by Sun et al (2018) of provincial panel data from China identified a crowding-out effect of natural resource dependence on human capital accumulation in the western and central regions of China. The same results were achieved by Douangngeune et al (2005) in Japan, South Korea, and Thailand; by Birdsall et al (2001) in South Korea and Brazil; and by Wang et al (2009) in China. Although the implications of vast natural resource endowments have been examined through their effects on primary outcomes, such as human capital, in many different countries, it is clear that the literature lacks studies in the Gulf region.…”
Section: Literature Reviewsupporting
confidence: 75%
“…Another empirical analysis by Sun et al (2018) of provincial panel data from China identified a crowding-out effect of natural resource dependence on human capital accumulation in the western and central regions of China. The same results were achieved by Douangngeune et al (2005) in Japan, South Korea, and Thailand; by Birdsall et al (2001) in South Korea and Brazil; and by Wang et al (2009) in China. Although the implications of vast natural resource endowments have been examined through their effects on primary outcomes, such as human capital, in many different countries, it is clear that the literature lacks studies in the Gulf region.…”
Section: Literature Reviewsupporting
confidence: 75%
“…Given the complexities of economic systems, policies on HRD and related areas are often embedded in the overall economic development policies. This situation was found in a recent study on Chinese management development policies (Wang, Rothwell & Sun, 2008). It is necessary for HRD researchers to have a basic understanding of major theories and models of development economics underlying current development policies, especially the ones related to HRD, while taking a systemic approach to policy analysis and implementation.…”
Section: Implications For Hrd Policy Studies and Theory Building Inquirymentioning
confidence: 98%
“…HRD scholars and practitioners may need to consider different strategies for research and practice to prepare workforce skills and competencies in the two different labor markets. In addition, research on approaches to bridge the dual labor markets may include (a) developing skills that may create rural entrepreneurs and niche industries; (b) preparing the rural workforce to be absorbed into the modern sector-necessary skills to achieve this transition may include not only basic literacy training but also skills necessary for the tasks required in these sectors, such as service skills; (c) studies on existing modern sector's HRD-related policy issues such as policies in management development and learning participation presented by Wang and Wang (2006), and Wang, Rothwell, and Sun (2008); and (d) evaluate policies, implementation processes, and outcomes of development policies.…”
Section: Implications For Hrd Policy Studies and Theory Building Inquirymentioning
confidence: 99%
“…Through analyzing citation network, keywords co-occurrences, and related patterns around research topics, we may identify existing HRD knowledge structure and evolving fronts. A recent study offers a relevant example on management learning and education (MLE) scholarship, a shared research area with HRD (Wang, Rothwell, & Sun, 2009). In exploring the legitimacy of MLE scholarship, Rynes and Brown (2011) examined four MLE journals’ contribution to the current state of MLE research with multiple indicators of scholarly legitimacy.…”
Section: Implications and Future Research In Hrdmentioning
confidence: 99%